Comparative Evaluation of Spectral Transmittance of Some Welding Glasses with ANSI Z87.1 - Rahmani, saeed; Akbarzadeh Baghban, Alireza; Nazari, Mohammadreza; Ghassemi-Broumand, Mohammad (Novelty in Biomedicine, 2016)
Background: Welding emits harmful rays to the eyes. We evaluate and compare the UV, blue light and IR transmittance characteristics of some currently available welding safety protectors with ANSI Z87.1 criteria. Materials and Methods: Three type of welding safety protectors (three of each type) have been evaluated for spectral transmittance. One-sample T-test was performed to establish is there a statistically significant difference between the standard criteria and UV, blue and IR regions for the welding protectors (α=0.05). Results: In ultraviolet (UV) (far and near) region, two types of the tested protectors (P1, P2) transmitted lower than the maximum allowable value specified in the standard (P<0.001). In infrared (IR) spectrum only one type (P3) transmitted lower than the maximum allowable value specified in the standard (P<0.001). In blue light region, all of the tested protectors transmitted lower than the maximum allowable value specified in the standard (P<0.001). Conclusion: Although all of the tested glasses could meet some parts of the criteria, but none of them could meet the complete spectral transmittance requirements of ANSI Z87.1.